Studi kasus penanganan masalah perundungan (bullying) di sekolah dan peran guru sebagai agen psikososial - Nurfaizah, Rosania (Maliki Interdisciplinary Journal, 2025)
Bullying in schools remains a serious challenge in education because it can disrupt students' psychological, social, and academic development. This study aims to explore the role of teachers as psychosocial agents in handling bullying cases in schools, through a case study at MTs Negeri 8 Banyuwangi. The findings indicate that teachers play a strategic role in preventing, detecting, addressing, and mitigating the effects of bullying through empathetic and educational approaches. Despite facing challenges such as insufficient training and limited support from the surrounding environment, the success of anti-bullying programs is significantly influenced by teachers' commitment and interprofessional collaboration within the school. These findings are reinforced by Bronfenbrenner's ecological theory, which positions teachers as part of the microsystem directly involved in creating a protective environment for students. Thus, strengthening teachers' capacities and systemic support from the school are key factors in creating a safe and bullying-free learning environment.